2015
DOI: 10.1371/journal.pone.0130649
|View full text |Cite
|
Sign up to set email alerts
|

Retention in HIV Care and Predictors of Attrition from Care among HIV-Infected Adults Receiving Combination Anti-Retroviral Therapy in Addis Ababa

Abstract: Background Patient retention in chronic HIV care is a major challenge following the rapid expansion of combination antiretroviral therapy (cART) in Ethiopia.Objective To describe the proportion of patients who are retained in HIV care and characterize predictors of attrition among HIV-infected adults receiving cART in Addis Ababa.Method A retrospective analysis was conducted among 836 treatment naïve patients, who started cART between May 2009 and April 2012. Patients were randomly selected from ten health-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
6
24
3
Order By: Relevance
“…In contrast to other settings in sub-Saharan Africa in which men have lower retention rates than women[710, 12, 13, 17, 18, 34], we did not observe any significant gender disparity. The streamlined care system employed by the clinics, which decreased the frequency and improved the efficiency of visits, could have particularly benefited men by reducing any disruption to employment or other work.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to other settings in sub-Saharan Africa in which men have lower retention rates than women[710, 12, 13, 17, 18, 34], we did not observe any significant gender disparity. The streamlined care system employed by the clinics, which decreased the frequency and improved the efficiency of visits, could have particularly benefited men by reducing any disruption to employment or other work.…”
Section: Discussioncontrasting
confidence: 99%
“…We excluded 1589 items for the reasons detailed in Figure . Thirty articles met inclusion criteria . Two studies reported results for children and adults separately.…”
Section: Resultsmentioning
confidence: 99%
“…Lower baseline CD4 counts or higher WHO stage of the disease was usually associated with higher rates of attrition [34], however in a number of articles, the authors noted that higher CD4 counts were related to poorer retention in care [27, 36]. Koole et al [30] and Mekuria et al [31] found that those with a poorer level of functionality (e.g. those who were bedridden) were also less likely to remain retained in medical care.…”
Section: Resultsmentioning
confidence: 99%